Autophagy Induced during Pancreatitis Promotes KRAS-Dependent Transformation in the Pancreas - Iovanna, Juan L. (Frontiers in Oncology, 2016)
Pancreatitis is an inflammatory disease that both facilitates and accelerates the transformation of pancreatic cells upon activation of the KRAS oncogene. Autophagy is proposed to be one of the cellular mechanisms contributing to pancreatic carcinogenesis, especially during initial stages in which the KRAS oncogene appears to play a key role. Autophagy is also strongly induced during pancreatitis by the overexpression of VMP1. We recently developed a genetically engineered mouse model in which the VMP1 protein is induced simultaneously with the activation of the oncogene KrasG12D specifically in the pancreas, by the addition of doxycycline to a water drink. Using this sophisticated animal model, we can affirm that pancreatic autophagy, induced during pancreatitis by the overexpression of VMP1, promotes the development of precancerous lesions when induced by the mutated KRAS. In addition, the treatment of these mice with chloroquine, an inhibitor of autophagic flux, reverses the effects of VMP1 in pancreatic cancer induced by the KRAS oncogene. Overall, these results bear both mechanistic and biomedical relevance for further understanding and potentially targeting pathways that are critical for initiating pancreatic carcinogenesis, particularly if associated with pancreatitis.